A new species of arboreal toad (Anura: Bufonidae: Chaunus) from Madidi National Park, Bolivia - Padial, José M.; Reichle, Steffen; Mcdiarmid, Roy; de La Riva, Ignacio (Zootaxa, 2006)
A new arboreal species of the Chaunus veraguensis group is described for the humid montane forest of Madidi National Park, in northern Bolivia. The new species differs from other species in the group by the combination small size, long and slender extremities, webbed hands, conspicuous tympanic membrane, well developed parotoid glands, absence of large glands on dorsum and extremities, nuptial excrescences of males composed of pungent spines on dorsal surface of thumb, greenish-brown coloration on dorsum with red warts in life, and green iris. It is only known from two nearby localities in the Serranía Eslabón, Department La Paz. An operational key for species in the C. veraguensis group is provided.